Estimation of aflatoxins in peanut or maize by enzyme linked immunosorbent assay - Shukla, Shruti (Bangladesh Journal of Pharmacology, 2016)
Aflatoxin are potentially toxic metabolites produced by microscopic fungi when grow on food. Hence, determining content of mycotoxins such as aflatoxin has significant pharmaceutical value. This study reports step-by-step visual demonstration of determination of aflatoxin contents in peanut and maize (corn)-based food samples through employing enzyme linked immunosorbent assay (ELISA). The method is based on direct competitive ELISA in a micro-well format which allows determination of exact amount of aflatoxin in food samples as parts per billion (ppb), and the results are calculated using Neogens Veratox data reduction software that converts the absorbance values into quantities. This visual experiment will certainly contribute knowledge regarding importance and applicability of the ELISA method for determining aflatoxin content in variety of food samples avoided of analytical issues such as sampling, laborious sample preparation, and critical selection of analytical methods. Video Clips of Methodology: Test sample preparation: 7 min 12 sec Full Screen Alternate Assay procedure: 5 min 23 sec Full Screen Alternate Measurement of absorbance by Tecan ELISA microtiter plate reader: 2 min 57 sec Full Screen Alternate